Clinical outcomes of ampullary neoplasms in resected margin positive or uncertain cases after endoscopic papillectomy - Sakai, Arata (World J Gastroenterol, 2019)
BACKGROUND: Endoscopic papillectomy (EP) for benign ampullary neoplasms could be a less-invasive alternative to pancreatoduodenectomy (PD). There are some problems and limitations with EP. The post-EP resection margins of ampullary tumors are often positive or uncertain because of the burning effect of EP. The clinical outcomes of resected margin positive or uncertain cases after EP remain unknown. AIM: To investigate the clinical outcomes of resected margin positive or uncertain cases after EP. METHODS: Between January 2007 and October 2018, all patients with ampullary tumors who underwent EP at Kobe University Hospital were included in this study. The indications for EP were as follows: adenoma, as determined by preoperative endoscopic biopsy, without bile/pancreatic duct extension, according to endoscopic ultrasound or intraductal ultrasound. The clinical outcomes of resected margin positive or uncertain cases after EP were retrospectively investigated. RESULTS: Of the 45 patients, 29 were male, and 16 were female. The mean age of the patients was 65 years old. Forty-one patients (89.5%) underwent en bloc resection, and 4 patients (10.5%) underwent piecemeal resection. After EP, 33 tumors were histopathologically diagnosed as adenoma, and 12 were diagnosed as adenocarcinoma. The resected margins were positive or uncertain in 24 patients (53.3%). Of these cases, 15 and 9 were diagnosed as adenoma and adenocarcinoma, respectively. Follow-up observation was selected for all adenomas and 5 adenocarcinomas. In the remaining 4 adenocarcinoma cases, additional PD was performed. Additional PD was performed in 4 cases, and residual carcinoma was found after the additional PD in 1 of these cases. In the follow-up period, local tumor recurrence was detected in 3 cases. Two of these cases involved primary EP-diagnosed adenoma. The recurrent tumors were also adenomas detected by biopsy. The remaining case involved primary EP-diagnosed adenocarcinoma. The recurrent tumor was also an adenocarcinoma. All of the recurrent tumors were successfully treated with argon plasma coagulation (APC). There was no local or lymph node recurrence after the APC. The post-APC follow-up periods lasted for 57.1 to 133.8 mo. No ampullary tumor-related deaths occurred in all patients. CONCLUSION: Resected margin positive or uncertain cases after EP could be managed by endoscopic treatment including APC, even in cases of adenocarcinoma. EP could become an effective less-invasive first-line treatment for early stage ampullary tumors.